Summertime scenes from provincial life - Coetzee, J. M. 1940- (Harvill Secker, 2009)
A young English biographer is working on a book about the late writer, John Coetzee. He plans to focus on the years from 1972-1977 when Coetzee, in his 30s, is sharing a run-down cottage in the suburbs of Cape Town with his widowed father. This, the biographer senses, is the period when he was 'finding his feet as a writer'.
Keywords: Coetzee, J. M. / 1940- / Fiction; Coetzee, J. M. <1940-> -- Fiction; Geschichte 1900-2000; Novelists, South African / 20th century / Biography / Fiction; Roman; Authors -- Fiction; Novelists, South African -- 20th century -- Biography -- Fiction; Englisch; Südafrika <Staat>; Biografie; Autobiographical fiction